APPLICATION OF MARCOS METHOD IN EVALUATION OF EFFICIENCY OF TRADE COMPANIES IN SERBIA - Лукић, Радојко (Economic Outlook, 2022)
The problem of measuring the efficiency of trade companies using methods is continuously relevant, significant and complex. With this in mind, this paper investigates the efficiency of trade companies in Serbia on the basis of the MARCOS method in order to consider the most realistic situation and improve in the future by taking relevant measures. According to the results of the MARCOS method, the top five trade companies in Serbia are in the following order: NELT CO. DOO BELGRADE, KNEZ PETROL DOO ZEMUN, DELHAIZE SERBIA DOO BELGRADE, LIDL SERBIA KD NOVA PAZOVA, and MERCATOR-S DOO NOVI SAD. Trade companies in Serbia that sell food products are well ranked. Factors that influenced this ranking of trade companies in Serbia are: general business conditions, interest rate, exchange rate, inflation, sustainable development, inflow of foreign direct investment, employment, living standards, digitalization of business, Covid-19. Also, the application of modern concepts of cost management, customer management, product category management, multi-channel sales, etc. Conducted similar research in other countries provides additional renewal to assess the efficiency of trade enterprises in Serbia and improve in the future by taking relevant measures.